1984
DOI: 10.1288/00005537-198405000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal carcinoma in childhood. Report of a case and review of the literature

Abstract: A rare cose of an 8½ year old boy with a stage III well differentiated squamous cell carcinoma of the larynx, which responded to chemotherapy and irradiation, is reported. It is the 56th cose in children up to 15 years of age and the 20th case in children 10 years old or younger reported since 1868. Carcinoma of the larynx in children has similar clinicopathological features to those of adult laryngeal carcinoma, but markedly differs as concerning sex incidence ratio. The main differential diagnosis is juvenil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…On the other hand, we recognize that due to a small number of patients, definitive treatment recommendations cannot be made at this time. Our cases, except one, had an early diagnosis and were treated according to the same parameters we use for adults, and our results were as good as other reported cases [21][22][23]. However, the patient with advanced tumor had an extremely unfavorable evolution, which reinforces the importance of staging in the evaluation of the prognosis of these cases and the need of an early diagnosis of this rare tumor.…”
Section: Discussionsupporting
confidence: 79%
“…On the other hand, we recognize that due to a small number of patients, definitive treatment recommendations cannot be made at this time. Our cases, except one, had an early diagnosis and were treated according to the same parameters we use for adults, and our results were as good as other reported cases [21][22][23]. However, the patient with advanced tumor had an extremely unfavorable evolution, which reinforces the importance of staging in the evaluation of the prognosis of these cases and the need of an early diagnosis of this rare tumor.…”
Section: Discussionsupporting
confidence: 79%
“…During this 12-year period when approximately 17,000 adult Lx or HP cancers were seen at our institute, only 6 (0.035%) were in the pediatric age group. Amongst the 68 children with laryngeal SCC reported in the literature [1][2][3][4][5][6][7][8][9][10][11][12], including three of the present series, various aspects of this disease, its treatment and outcome can be studied. The details are, however, not available for each reported case.…”
Section: Discussionmentioning
confidence: 99%
“…As expected from the multistep carcinogenesis model, it is very rare in children. Since 1868, only 65 cases of childhood SCC of larynx [1][2][3][4][5][6][7][8][9][10][11][12] and 2 cases of hypopharynx [11,13] have been reported, all as isolated case reports. We present the largest series of six consecutive children below the age of 16 years with laryngeal (Lx) or hypopharyngeal (HP) SCC seen at a single institute from 1989-2000.…”
mentioning
confidence: 99%
“…The prognosis of laryngeal carcinoma in adolescents is unclear because survival rates have not been reported according to tumour stage due to the scarcity of cases [10]. Recently, studies have suggested that prognosis may be affected by the presence of chromosomal translocation (15;19) or the presence of HPV DNA within the tumor cells.…”
Section: Resultsmentioning
confidence: 99%